2022
DOI: 10.1038/s41598-022-16745-8
|View full text |Cite
|
Sign up to set email alerts
|

Ancient mitochondrial diversity reveals population homogeneity in Neolithic Greece and identifies population dynamics along the Danubian expansion axis

Abstract: The aim of the study is to investigate mitochondrial diversity in Neolithic Greece and its relation to hunter-gatherers and farmers who populated the Danubian Neolithic expansion axis. We sequenced 42 mitochondrial palaeogenomes from Greece and analysed them together with European set of 328 mtDNA sequences dating from the Early to the Final Neolithic and 319 modern sequences. To test for population continuity through time in Greece, we use an original structured population continuity test that simulates DNA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 72 publications
(116 reference statements)
3
10
0
Order By: Relevance
“…By dividing our estimated effective size (in number of chromosome copies) by two to get the number of effective individuals and then multiplying the result by three (53), we were able to roughly estimate a FA census size of approximately 0.27 individuals/km 2 (95 HDI = 0.19-0.35) within a deme of 100x100 km 2 . This estimate is close but lower than the estimate of Silva et al (30), based on ancient mitochondrial data (0.46 individuals/km 2 ) and in line with the upper range (0.6 individuals/km 2 ) estimated by Zimmermann et al (54) for the Linear Pottery culture (LBK).…”
Section: Limited Population Competition and Population Effective Size...supporting
confidence: 86%
See 2 more Smart Citations
“…By dividing our estimated effective size (in number of chromosome copies) by two to get the number of effective individuals and then multiplying the result by three (53), we were able to roughly estimate a FA census size of approximately 0.27 individuals/km 2 (95 HDI = 0.19-0.35) within a deme of 100x100 km 2 . This estimate is close but lower than the estimate of Silva et al (30), based on ancient mitochondrial data (0.46 individuals/km 2 ) and in line with the upper range (0.6 individuals/km 2 ) estimated by Zimmermann et al (54) for the Linear Pottery culture (LBK).…”
Section: Limited Population Competition and Population Effective Size...supporting
confidence: 86%
“…This means that at each generation, when HGs and FAs coexist in a cell, a fraction γ of the contact between them results in admixture. This leads to the passage of HG genes into the FA population, and thus to gene flow from HG to FA, following previous simulation studies (29,30). Note that the model does not distinguish whether this gene flow is due to the adoption of agriculture by HGs, the assimilation of HGs into the agricultural population, or mixed encounters between individuals from the two populations resulting in the birth of a child in the FA population.…”
Section: Spatially Explicit Simulationsmentioning
confidence: 90%
See 1 more Smart Citation
“…In Europe, a prominent genetic transition occurred during the spread of early Neolithic farmers, when they partially replaced Paleolithic/Mesolithic hunter-gatherers [i.e., the so-called Neolithic transition ( 33 , 34 , 35 )]. At least along the Danube route from Anatolia to Central Europe, paleogenetic analyses have revealed that the first stage of the Neolithic transition occurred through the migration of FAs, followed by admixture with local HGs in a second stage, e.g., ( 32 , 33 , 35 , 47 ). This transition began in the Fertile Crescent ~11,000 years BP ( 48 ), and its consequences on the distribution of NE ancestry have been weakly explored thus far ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…The present territory of modern Greece as a Mediterranean entity was unavoidably influenced during the Neolithic expansion era by the arrival of immigrant farmers from the Near East [ 46 ]. During this distinctive period, along with the obvious innovative stone-age technologies that were brought to the indigenous population, new genomic variations were also introduced, as a result of multi-phase mixing contributing in that way to their genetic distinctiveness [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%